Máquinas eletrostáticas no ensino fundamental: uma proposta educacional para motivar o ensino de física conduzida por uma aprendizagem sociocultural - Lessa, Jorge Luís Moura (Universidade Federal Rural do Semi-Árido, 2020)
In this work we performed an analysis in the two versions of the book Experimental and Historical Foundations of Electricity in Assisi and in Vygotsky's socio-historical theory to develop a pedagogical activity related to the teaching of Physics in science for students of the eighth grade of elementary school. In their conversion in the classroom, workshops were formatted, through texts and experimental practices with interactions of students socializing with colleagues and the teacher their cognitive development. In this action, it was possible to talk about electrostatic machines and point it out as a possible methodological strategy in the didactic transposition of the electrostatic content. The didactic sequence dealt qualitatively with the concepts of electric charge, electric field and capacitors with students divided into groups, to attend theoretical classes, read and interpret thematic texts, as well as, to build and test experiments that are easy to be developed in the classroom environment. In this work proposal, low-cost materials were used to generate the educational product achieved through three electrostatic devices: electrophores, a Wimshurst machine and Kelvin's electric rain. Educational support allowed the construction of knowledge within the ZDP with social interactions, in which the student can associate the phenomena present in the educational product with theory, as well as with the electrical and electronic objects of his / her life. The teaching model presented makes it possible in the teaching action an interaction with greater appreciation of social relations linked to the electrostatic theme, facilitating the understanding of the content. The results of the post-test and the evaluation questionnaire indicate effective evidence in the student's learning and interest in Physics.
Keywords: Eletrostática; Oficinas; Eletróforo; Máquina eletrostática; Aprendizagem sociocultural; Electrostatics; Workshops; Electrophorus; Electrostatics machine; Socio-cultural learning; CIENCIAS EXATAS E DA TERRA::FISICA